Alteração judicial de políticas públicas: adequação do processo coletivo estrutural e falta de condições da ação em demandas pseudoindividuais - Nassar, Marcos (2024)
The aim of this study is to examine whether the Brazilian procedural system establishes a given procedural path that is appropriate for handling disputes whose resolution necessarily involves changing public policies, to the detriment of other paths. The deductive method is predominantly used, based on bibliographical research. The initial objective is to address, as a prerequisite for the rest of the work, the justiciability of social-economic rights, including those arising from legal principles, through, if necessary, modification of the respective public policy. Then it is addresses the current model of judicialization in this field, embodied in the myriad of individual lawsuits verified throughout the country and fueled by the daily filing of new lawsuits seeking, in most cases, health benefits not provided for in the corresponding public policy, only in favor of the individual plaintiff, or a place in a daycare center also only for the benefit of the plaintiff. The aim is to present the consequences that this model has produced in relation to the implementation of substantive law, notably with regard to the legal principle of equality, that is the source value of fundamental social-economic rights, as well as to the detriment of the organization and rationality of the expenditure of limited resources for the implementation of public policies, an activity for which one cannot dispense with an overview of the problems and data involved, whose apprehension is impractical in each of the hundreds of thousands of existing individual lawsuits. Next, from the perspective of procedural instrumentality, it is examined whether class actions are more appropriate for the jurisdictional assessment of such disputes, whether in light of the legal principle of equality, given the breadth of the class actions effects, or in light of the very nature of the right to change a given public policy. To this end, the intent is to verify whether a social-economic right whose satisfaction requires modification of the corresponding public policy has a transindividual, specifically diffuse, nature. In continuation, still from the perspective of procedural instrumentality, the objective is to show that frequently these disputes reveal not only a collective but also a structural nature. Therefore, the plan is to outline what is understood as structural litigation, which procedural techniques such form of disputes often require for their adequate adjudication (techniques that characterize what is called structural suit, a type of class action), as well as whether Brazilian civil procedural law offers these techniques. Finally, the standing to sue in individual lawsuits aimed at changing public policies will be examined. The intention is to verify whether the standing to sue analysis can contribute to the matter of changing public policies by judges, especially from the perspective of procedural instrumentality that guides this doctoral thesis. For this purpose, after explaining standing to sue in Brazil, its application on the aforementioned demands is examined, as well as the compatibility of this approach with access to justice